FITOREMEDIASI AIR TERCEMAR LOGAM KROMIUM DENGAN MENGGUNAKAN Sagittaria lancifolia DAN Pistia stratiotes SERTA PENGARUHNYA TERHADAP PERTUMBUHAN KANGKUNG DARAT (Ipomea reptans) - Lia Kurniawati Odar Serang; Eko Handayanto; Ridesti Rindyastuti (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2018)
Chromium (Cr) is commonly found in water containing waste of batik industry. Several aquatic plants that usually become weeds, such as Sagittaria lancifolia and Pistia stratiotes, can be utilized in the remediation of heavy metal contamination in aquatic environment. The objective of this study was to elucidatethe potential of aquatic plants of Sagittaria lancifolia and Pistia stratiotes in the phytoremediation of chromium contaminated water and its effect of growth of water spinach (Ipomea reptans). The results of showed that Sagittaria lancifolia and Pistia stratiotes were potential to be used as phytomediators and they were able to reduce Cr levels in contaminated water in treatments of PSM1 (Pistia stratiotes + 2 ppm Cr) by 1,757 ppm or 87,85%, PSM2 (Pistia stratiotes + 5 ppm Cr) by 4,379 ppm or 87,59%; SLM1 (Sagittaria lancifolia + 2 ppm Cr) by 1,785 ppm or 89,23%; SLM2 (Sagittaria lancifolia + 5 ppm Cr) by 4,032 ppm or 80,64%. The concentration of Cr on the water after phytoremediation had a significant impact on the Cr levels contained in water spinach. The treatment of SLM1 (Sagittaria lancifolia + 2 ppm Cr) had the highest Cr absorption score in water spinach at 0,184 ppm, while the treatment of TTM1 (control + 2 ppm Cr) had the lowest Cr absorption score at 0,098 ppm. The results of this study also indicated that water spinach was not safe for consumption as the Cr level in the plant was greater than the threshold limit of Cr level in food of 0,05-0,2 ppm.Â